2021
DOI: 10.1177/21582440211047248
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Ownership Structure on Earnings Management: The Case of Vietnam

Abstract: This study is conducted to investigate the impact of ownership structure on earnings management in emerging countries and Vietnam as the case study. In this research, we explore how three components of ownership structure, including ownership concentration of managers, foreign ownership ratio, and state ownership ratio, influence earnings management. In addition, we also consider whether ownership structure influences profit management during financial constraints. REM, FEM, GLS, and GMM regression methods are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 57 publications
0
6
1
2
Order By: Relevance
“…Susanto et al (2019) used data from 132 nonfinancial enterprises listed on the Indonesia Stock Exchange to show that institutional ownership and tax aggressiveness have a positive and significant impact on earnings management, whereas firm size, director independence, audit quality, and managerial ownership have no bearing. However, the results of this study were in contrast with those of Tran and Dang (2021), who proved the impact of firm size, financial leverage, profitability, and audit quality on earnings management practices. Supardi and Asmara's (2018) findings demonstrated that firm size has no discernible impact on earnings management, which was demonstrated using a sample of businesses registered on the Indonesia Stock Exchange.…”
Section: Literature Reviewcontrasting
confidence: 99%
“…Susanto et al (2019) used data from 132 nonfinancial enterprises listed on the Indonesia Stock Exchange to show that institutional ownership and tax aggressiveness have a positive and significant impact on earnings management, whereas firm size, director independence, audit quality, and managerial ownership have no bearing. However, the results of this study were in contrast with those of Tran and Dang (2021), who proved the impact of firm size, financial leverage, profitability, and audit quality on earnings management practices. Supardi and Asmara's (2018) findings demonstrated that firm size has no discernible impact on earnings management, which was demonstrated using a sample of businesses registered on the Indonesia Stock Exchange.…”
Section: Literature Reviewcontrasting
confidence: 99%
“…The formula used in this study was previously used in the study of Dang et al (2017), Tran and Dang (2021) and Kalbuana, et al (2022):…”
Section: Profitabilitymentioning
confidence: 99%
“…Growth Rate (GROWT) Control +/-Calculated as (Revenue t -Revenue t-1 ) / Revenue t-1 (Tran & Dang, 2021).…”
Section: Leverage (Lev)mentioning
confidence: 99%